DISCOURSE IN DIVERSE ASSESSMENT TECHNIQUES EMPLOYED BY LANGUAGE TEACHERS - Ida Ayu Made Sri Widiastuti; I Gde Putu Agus Pramerta; I Nyoman Suparsa; Ni Luh Sukanadi (Denpasar Institute, 2020)
Classroom assessment is a process of collecting and utilizing information on student learning outcomes carried out by teachers. The process of collecting and utilizing this information is used to determine the level of achievement of students towards competency attainment. The results of the assessment can provide an overview of the competence and progress of the students. This study explores the principles of classroom-based assessment carried out by teachers in real classroom settings. The study revealed that teachers employed various assessment techniques due to their various understanding of classroom assessment. Teachers had different views on how the implementation of classroom assessment and methods of assessments. Several forms of assessment conducted by teachers include a collection of a portfolio, product, project, performance, and written tests. However, some teachers still conducted those forms of assessment inappropriately. This study implies that further educational training on classroom assessment should be developed by educational stakeholders.